2013
DOI: 10.1002/jcb.24565
|View full text |Cite
|
Sign up to set email alerts
|

MiR‐23a in amplified 19p13.13 loci targets metallothionein 2A and promotes growth in gastric cancer cells

Abstract: Copy number variation (CNV) and abnormal expression of microRNAs (miRNAs) always lead to deregulation of genes in cancer, including gastric cancer (GC). However, little is known about how CNVs affect the expression of miRNAs. By integrating CNV and miRNA profiles in the same samples, we identified eight miRNAs (miR-1274a, miR-196b, miR-4298, miR-181c, miR-181d, miR-23a, miR-27a and miR-24-2) that were located in the amplified regions and were upregulated in GC. In particular, amplification of miR-23a-27a-24-2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
35
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(40 citation statements)
references
References 30 publications
4
35
1
Order By: Relevance
“…Many miRNAs are closely associated with GC, but knowledge of their abnormal expression and potential role in GC is inadequate. Eight miRNAs (miR1274a, miR196b, miR4298, miR181c, miR23a, miR27a, and miR-24-2) were reported to be highly expressed in GC tissue [9]. Combining this result with bioinformatics analysis on Prdx-6, which has been intensively investigated in our previous study [8], we selected miR-24-3p for further study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many miRNAs are closely associated with GC, but knowledge of their abnormal expression and potential role in GC is inadequate. Eight miRNAs (miR1274a, miR196b, miR4298, miR181c, miR23a, miR27a, and miR-24-2) were reported to be highly expressed in GC tissue [9]. Combining this result with bioinformatics analysis on Prdx-6, which has been intensively investigated in our previous study [8], we selected miR-24-3p for further study.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, bioinformatics prediction indicated that there are five miRNAs that might regulate Prdx-6 expression level (hsa-miR-24, hsa-miR-186, hsa-miR-149, hsa-miR-124, and hsa-miR-506). Based on the integrated analysis of copy number variations (CNVs), genomic alterations, miRNA expression profiling, microRNA 24 drew our attention and it has two gene subtypes—miR-24-3p, miR-24-5p [9]. After preliminary experiments, miR-24-3p was found to be highly expressed in GC.…”
Section: Introductionmentioning
confidence: 99%
“…143 By integrating CNV and miRNA profiles in the same samples, the authors identified eight miRNAs (miR--1274a, miR-196b, miR-4298, miR-181c, miR-181d, miR-23a, miR-27a and miR-24-2) that were located in the amplified regions and were upregulated in GC. The amplification of miRNAs were confirmed by real-time PCR and in situ hybridization assays.…”
Section: Cnvs On Other Chromosomesmentioning
confidence: 99%
“…miRNAs functioned as oncogenes or tumor suppressors by regulating different target gene expression in different cancers. miR-9, miR-22, and miR-146a had all been shown to act as tumor suppressors [911], whereas miR-19, miR-23a, and miR-301a had been shown to function as oncogenes [1214]. These studies suggested that dysregulation of miRNAs might be involved in carcinogenesis and cancer progression.…”
Section: Introductionmentioning
confidence: 99%